Evaluating Character Education Programs to Enhance Spiritual Resilience among Theology Students: A Kirkpatrick Model Analysis at STT Sangkakala - Ester Uru Hida; Bambang Ismanto; Tri Widiarto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Character education in theological higher education is expected to form students who are not only academically competent but also spiritually resilient, morally responsible, and prepared for ministry. However, the effectiveness of such programs is often assumed rather than systematically evaluated. This study evaluates the character education program at STT Sangkakala in enhancing the spiritual resilience of theology students using the Kirkpatrick Model. Employing an explanatory sequential mixed-methods design, quantitative data were collected through questionnaires from 65 active theology students, while qualitative data were obtained through interviews, observations, and document analysis involving institutional leaders, lecturers, dormitory supervisors, students, alumni, and church pastors. The evaluation focused on four levels: reaction, learning, behavior, and results. The findings show that the reaction level reached 79.09% with a mean score of 3.16, indicating positive student responses to the program. The learning level achieved the highest score, reaching 81.70% with a mean of 3.27, showing strong improvement in students’ understanding of Christian character values and spiritual resilience. The behavior level reached 76.49% with a mean of 3.06, indicating initial behavioral transfer in spiritual discipline, responsibility, dormitory life, and ministry practice. However, the results level reached only 77.75% with a mean of 3.11, below the 80% success criterion, indicating that spiritual resilience was not yet fully stable or sustainable. This study contributes to theological education by showing that character education must move beyond value understanding toward continuous mentoring, reflective ministry practice, dormitory-based formation, and longitudinal evaluation.